The Influence of Problem Solving Model Toward Students’ Critical Thinking Skills - Nindya Ananda Latifa; Heffi Alberida (Bioeducation Journal, 2019)
The aims of this study was to find whether there was an influence of the Problem Solving Model towards critical thinking skills of students of grade XI in SMAN 9 Padang. A Quasi Experiment method with The Post-test Control Group Only Design was used in this study. Students were grouped in an experimental group (Problem Solving model) and a control group (Direct intruction). The data from a test were analyzed using t-test with a=0,05. The findings showed that there was a significant difference of critical thinking skills enhancement in experimental group than the control group.